2022
DOI: 10.1055/s-0041-1742110
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Predictive Factors for Successful Vaginal Delivery after a Trial of External Cephalic Version: A Retrospective Cohort Study of 946 Women

Abstract: The corrected Objective section should read as: Objective Our aim was to find the factors which predict a vertex presentation vaginal delivery (VD) in women who are admitted for a trial of external cephalic version (ECV).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The remaining 11 articles were completely independent from each other; two of these articles proposed two models each 36,37 , while the remaining 9 proposed a single model each [38][39][40][41][42][43][44][45][46] (Figure 2). Two of the articles had an erratum: one was trivial 40,47 and only modi ed a sentence in the abstract, while the other was a correction of a gure describing the decision tree model 41,48 . See Appendix 4 for notes on how distinct models were counted in certain circumstances.…”
Section: Relationships Between Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 11 articles were completely independent from each other; two of these articles proposed two models each 36,37 , while the remaining 9 proposed a single model each [38][39][40][41][42][43][44][45][46] (Figure 2). Two of the articles had an erratum: one was trivial 40,47 and only modi ed a sentence in the abstract, while the other was a correction of a gure describing the decision tree model 41,48 . See Appendix 4 for notes on how distinct models were counted in certain circumstances.…”
Section: Relationships Between Articlesmentioning
confidence: 99%
“…Of these articles, two were from the same team of authors and used the same dataset; Anand 2019 used the dataset to create a model predicting cephalic position after the ECV, while the Palepu 2021 created a model to predict vaginal delivery 30,31 The remaining 11 articles were completely independent from each other; two of these articles proposed two models each 32,33 , while the remaining 9 proposed a single model each [34][35][36][37][38][39][40][41][42] (Figure 2). Two of the articles had an erratum: one was trivial 36,43 and only modi ed a sentence in the abstract, while the other was a correction of a gure describing the decision tree model 37,44 . See Appendix 4 for notes on how distinct models were counted in certain circumstances.…”
Section: Relationships Between Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 11 articles were completely independent from each other; two of these articles proposed two models each 36,37 , while the remaining 9 proposed a single model each [38][39][40][41][42][43][44][45][46] (Figure 2). Two of the articles had an erratum: one was trivial 40,47 and only modified a sentence in the abstract, while the other was a correction of a figure describing the decision tree model 41,48 .…”
Section: Relationships Between Articlesmentioning
confidence: 99%
“…The results of the study quality assessment based on the signaling questions are shown in Table 4. Out of 17 new articles, 10 studies were identified as having low overall risk of bias and high study quality 22,[33][34][35][36]39,41,[44][45][46] , 6 studies were identified as having moderate bias and moderate study quality 29,37,38,42,43,47 , and 1 was considered to have high bias and low quality 30 . This is in addition to Velzel et al's assessment of the 8 prior articles of which 4 were low risk of bias and high study quality and 4 were moderate risk of bias and study quality 10 .…”
Section: Quality and Biasmentioning
confidence: 99%